On the (Re)Construction of Corruption in the Media: A Critical Discursive Approach - Breit, Eric (Journal of business ethics, 2010)
Although corruption has become a hot topic in organizational research, few studies have examined how it is socially constructed. To partially bridge this gap, the present paper takes a critical discursive perspective on the representation of corruption in the media. The empirical focus is on the media coverage of a corruption scandal that revolved around two instances of formal corruption charges and successive acquittals. Based on the analysis, the paper exemplifies how the media makes sense of and gives sense to controversial activities in response to changing and at times contradictory information. In particular, the paper highlights interplay between four dominant discourses—transgression, political, public scapegoating, and individualistic—that that were mobilized throughout the media coverage. These discourses were intimately linked with wider dynamics between problematizing and restorative media framings and thus provided crucial means of reconstructing and reformulating the (il)legitimacy of the reported activities throughout the scandal. While the findings are context specific, this study suggests that similar interplay and dynamics are important aspects of media sensemaking around controversial activities related to corruption.